Trends in the Mortality, Deaths, and Aetiologies of Lower Respiratory Infections Among 204 Countries from 1991 to 2021: An Updated Systematic Study - Meichen Li; Min Liu; Jue Liu (Viruses)
Lower respiratory infections (LRIs) persist as a major global health threat. This study analyses the 1991–2021 trends in LRI mortality, deaths, and aetiologies across 204 countries using Global Burden of Disease 2021 data, aiming to evaluate the disease burden of LRIs and provide evidence-based guidance for prevention strategies. To quantify the temporal trends, the annual percentage change was estimated (EAPC) using linear regression modeling. Globally, the ASMR for LRI decreased by an average of 2.29% annually (95% CI: 2.16–2.42%). While ASMR decreased in 20 of the GBD regions, mortality rates in Southern Latin America increased (EAPC = 1.32, 95% CI: 0.98–1.67). The LRI burden remains the heaviest in low SDI regions and sub-Saharan Africa. LRIs continue to cause high mortality in children and the elderly. Mortality in children decreased rapidly, while mortality in the elderly declined more slowly. Streptococcus pneumoniae was the leading cause of LRI-related deaths, followed by Staphylococcus aureus and Klebsiella pneumoniae. LRIs remain a leading cause of global mortality, especially in low SDI regions, and among children and the elderly. Future research on LRIs and the development of effective prevention and control strategies are essential to reduce the disease burden of LRIs.